Indocyanine green fluorescence-guided laparoscopic colorectal cancer surgery with prophylactic retrograde transileal conduit ureteral catheter placement after previous total cystectomy: a case report - Teppei Kamada; Yuichi Nakaseko; Masashi Yoshida; Wataru Kai; Junji Takahashi; Keigo Nakashima; Norihiko Suzuki; Hironori Ohdaira; Eigoro Yamanouchi; Yutaka Suzuki (Surgical Case Reports, 2021)
Abstract Background Iatrogenic ureteral injury (UI) is a potentially serious complication of colorectal cancer surgery. Performing perioperative placement of ureteral stents or intraoperative fluorescence navigation surgery for the ureter using indocyanine green (ICG) has been employed as a method of preventing UI. However, transileal conduit stent placement has been considered challenging because it is difficult to identify the ureteral orifice due to the anatomical changes caused by a previous surgery. We report a case in which laparoscopic colectomy was safely performed using a combination of prophylactic transileal conduit ureteral catheter placement and intraoperative ICG fluorescence navigation surgery. Case presentation A 75-year-old man presented to our hospital complaining of vomiting and abdominal distension. He had a history of open total cystectomy and ileal conduit urinary diversion 11 years prior to admission. Computed tomography confirmed colon dilation with fecal impaction from the ascending colon to the sigmoid colon and wall thickening in the sigmoid colon. Colonoscopy during the transanal ileus tube insertion revealed a Borrmann type II tumor with circumferential stenosis 10 cm distal to the junction between the descending colon and the sigmoid colon. The patient was diagnosed with colorectal ileus due to obstructive sigmoid colon cancer and underwent transanal ileus tube insertion. Severe intra-abdominal adhesions were expected due to the previous total cystectomy, and the left ureter was near the sigmoid colon tumor; therefore, prophylactic retrograde transileal conduit ureteral catheter placement was performed one day before the elective surgery. During the operation, 20 ml (5.0 × 10–2 mg/ml) ICG was administered from the transileal conduit ureteral catheter, and ICG fluorescence of the ureter was observed in the retroperitoneum. Laparoscopic Hartmann's operation was successfully performed, confirming ureter fluorescence. The operation time was 231 min, with 5 mL of intraoperative bleeding. The ureteral catheter was removed 3 days after the operation. The patient’s postoperative course was good with no complications, and he was discharged on postoperative day 7. Conclusions Prophylactic transileal conduit ureteral catheter placement and ICG fluorescence navigation surgery were effective in performing laparoscopic colorectal surgery with severe adhesions after urinary diversion.